Oxford english for information technology : - Glendinning, Eric H. (Oxford University Press, 2006)
This is an easy-to-use yet serious course for students who are specializing in computing and information technology. It reviews and offers practice of grammar and functions that are appropriate for the needs of IT specialists. All four language skills are consolidated and developed through a variety of authentic, interesting, and topical texts and visual materials. The "Teacher's Book includes a full introduction to the topics in each unit for teachers who are not IT specialists. It provides notes, and an answer key, listening script and photocopiable progress tests. The "Audio Program, available on "CD or "Cassette features all of the dialogues, interviews, discussions and listening tasks.